Politiques du logement et intégration au Mexique : de la promotion publique à la promotion immobilière privée - Emilio Duhau (Cahiers des Amériques Latines)
In Mexico, at the beginning of the XXIth century, most of households are property owners; 78.3% of them by the year 2000, according with data becoming from the XIIth Population and Housing Census. Taking account that this fact is widely linked with housing policies implemented by the Mexican state during de last thirty years, this paper offers a number of evidences and reflections concerning the role of public housing policies in urban and social integration processes, as well as a preliminary evaluation of neo-liberal housing policies reorientation during the last decade of the XXth century, and its impacts on such processes.